Human papillomavirus infections and renal transplantation: a review - Baez, Camila F.; Cossatis, João J.; Afonso, Larissa A.; Varella, Rafael B.; Cavalcanti, Silvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
The immune suppressive therapy in renal allograft recipients provides a favorable environment to the development of viral infections. Among them, human papillomavirus (HPV) infections are usually related to potential life-threatening mucocutaneous neoplasias. Data from clinical surveys suggest that transplant recipients may have up to 5-fold increased risk of developing multiple malignancies due to the increased susceptibility to persistent HPV infection. High risk HPV induced oncogenesis is a multi-step process in which a persistent infection is the initiating causative event, though subsequent genetic and epigenetic alterations may be necessary for malignant transformation. The main tumoral types associated with persistent HPV infection are anogenital, oral and skin cancers, common conditions in transplant recipients and responsible for substantial morbidity and mortality. Since prophylactic vaccines with high rates of efficacy have been approved for human population, studies to evaluate its immunogenicity and efficacy should be considered for long-term survivors after allogeneic transplantation. Hence, we conducted an extensive revision published data for the last 10 years regarding the theme. To achieve our objectives, we searched in diverse data basis such as Lilacs, ScIELO, Medline, Scopus. We concluded that, concerning the increase in the population of transplant recipients as well as in the incidence of HPV associated diseases, measures for prevention and control are necessary, and include capaciting human resources and the use of last generation methodologies of diagnosis and prophylaxis.